Special Exercises Using Medicine Balls On The Development Of Lower and Upper Extremities ' Explosive Power and Some Static situations in Soccer - Aobais, Mofq (Journal of Physical Education, 2016)
Training using medicine ball is considered on e of the best training aids that can develop the players' skill and physical levels due to their ability to develop the muscular strength of players according to correct skill performance. The research aims at designing exercises using medicine balls of different weights. The researcher hypothesized statistical significant differences between pre and posttests in skill variables for both experimental and controlling groups in favor of posttests. The researcher used the experimental method and a training program. The data was collected and treated using proper statistical methods. The researcher concluded that exercises using medicine balls of different weights have positive effects in developing skills. Finally the researcher recommended using scientific bases in designing exercises as well as paying attention to using medicine balls of different weights in training due to their positive effects on developing skills.